1989
DOI: 10.1051/alr:1989010
|View full text |Cite
|
Sign up to set email alerts
|

Suitability of brackish water tilapia species from the Ivory Coast for lagoon aquaculture. II - Growth and rearing methods

Abstract: In intensive culture, the two species of brackish water tilapia, T. guineensis and S. melanotheron, have proved disappointing. Even under most favourable conditions, i. e. the monosex male culture of S. melanotheron, a poor growth rate (about O. 5g. d-') and a mediocre feed conversion do not presage a profitable aquaculture exploitation. On the other hand, extensive culture trials using the original "acadja-enclosure" technique have given very encouraging resu1ts.A nnual fish yields of more than 8 t/ha, includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

1991
1991
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 6 publications
0
21
0
1
Order By: Relevance
“…5a). These observations are related to the frequent growth differences among individuals of several cichlid species populations (Hecht 1980;Pauly et al 1988;Legendre et al 1989;Booth et al 1995;Panfili et al 2004). Nevertheless no clear interpretation can be given to explain such differences in otolith GI for S. melanotheron (Fig.…”
Section: Difficulties Associated With Otolith Interpretation In the Tmentioning
confidence: 99%
“…5a). These observations are related to the frequent growth differences among individuals of several cichlid species populations (Hecht 1980;Pauly et al 1988;Legendre et al 1989;Booth et al 1995;Panfili et al 2004). Nevertheless no clear interpretation can be given to explain such differences in otolith GI for S. melanotheron (Fig.…”
Section: Difficulties Associated With Otolith Interpretation In the Tmentioning
confidence: 99%
“…Pariselle, 1994 ;Pariselle et Euzet, 1994, 1995, 1996, N'Douba, 2000Gnayoro, 2008), aucune étude n'a été consacrée à la dynamique saisonnière des parasites du tilapia Sarotherodon melanotheron melanotheron. Cette sous-espèce fait l'objet d'une attention toute particulière en aquaculture (Legendre et al, 1989) du fait qu'elle présente un intérêt économique (Hem & Avit, 1994). En outre, dans le lac de barrage d'Ayamé I, situé au Sud Est de la Côte d'Ivoire, ce poisson représente actuellement plus de 50 % des captures des pêches commerciales (Gourène et al, 1999).…”
Section: Introductionunclassified
“…The few nutritional studies conducted on this species shows that the growth rates which have been obtained thus remain poor (Legendre 1983;Campbell 1987;Legendre et al 1989), especially when compared with those observed for other tilapia species already used in aquaculture. Consequently, research directed towards this species has not been encouraging and has therefore created a vacuum that does not improve the growth performance of this tilapia species which is believed to be of great aquaculture potentials most especially in the brackish water zone of Nigeria.…”
Section: Conclusion and Recommendationmentioning
confidence: 97%
“…Besides, Legendre et al (1989) reported that intensive culture of brackish water tilapia, T. guineensis have proved disappointing even under most favourable conditions. Copepods are increasingly seen as a supplementary feed to rotifers and Artemia in the culture of 'difficult' marine fish (Battaglene and Fielder 1997).…”
Section: Calanoid Copepodsmentioning
confidence: 99%
See 1 more Smart Citation